Evaluation of Utilization Levels and User Satisfaction of Cold Chain and Solar Packed Facilities Fisherman Dealers Goto Fish Landing Base, Tidore Islands City - Iksan, Kusdi Hi; Abd. Latif, Hamid; Wahidin, Nurhalis; Karman, Amirul; Taeran, Imran; Djamhur, Martini (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
Based on initial information from fishermen and fish buyers that the fulfillment of the needs for ice blocks and fuel oil for fishermen to go to sea at the Goto Fish Landing Base (PPI) is experiencing problems. The port has not been able to meet the demand for ice blocks and fuel oil (BBM) so fishermen have to buy from outside the port. In order to optimally serve the needs of users at PPI Goto City, Tidore Islands, it is necessary to improve cold chain facilities and SPDN supported by scientific studies on the status of facility utilization and user satisfaction levels. This study aims to analyze the level of utilization and satisfaction of cold chain facilities and SPDN users at PPI Goto, Tidore Islands City. The research was conducted at PPI Goto City, Tidore Islands, for 3 months, from February to April. Field data collection for 1 week, on March 2-9, 2021. The research uses the case study method. The results showed that the ice factory facilities could not serve the needs of fishermen because they were in a damaged condition as well as the SPDN facilities could not serve the needs of fishermen because there was no fuel supply from Pertamina. All stakeholders (masters, fishermen, and entrepreneurs who buy fish) expressed dissatisfaction with the service of ice factory facilities and SPDN, while for ABF and cold storage facilities, respondents stated that they were very satisfied.